Assessing Stressors and Coping Mechanisms of International Nursing Students in the Country of Georgia - Crawford, Kimberley A.; Jojua, Khatuna; Gogashvili, Maia (Caucasus Journal of Health Sciences and Public Health, 2019)
International nursing students in the country of Georgia face many stressors beyond native Georgians in the same context. These students who have chosen to move to a new country where they do not speak the language, have different food and climate and even look very differently than the local population have developed different coping mechanisms that are both effective and not effective. This descriptive study provides a basic assessment of stressors and coping mechanisms currently being experienced by this international community. This is the first of many articles discussing this topic.